Penile length of term newborn infants in multiracial Malaysia. - Ting, Tzer Hwu; Wu, LooLing (Singapore Medical Association, 2009)
Introduction: Micropenis may be an important sign of underlying hypogonadism or pituitary hypofunction in the neonatal period. Penile lengths of normal newborns have been reported in many Western populations. However, the data may not be applicable in the Asian or the multiracial Malaysian population. Our study aimed to establish the normal penile length and testicular volume in term newborn infants in the major ethnic groups in Malaysia.